Strangers, Gods and Monsters: Interpreting Otherness - Johnson, Bradley A. (Literature and theology, 2004)
Strangers, Gods and Monsters: Interpreting Otherness RichardKearney London Routledge 2003 x + 294 pp. £ 55 (£16.99 pb)/$80 ($24.95 pb)